2021
DOI: 10.1002/wcs.1560
|View full text |Cite
|
Sign up to set email alerts
|

Emotional contagion in nonhuman animals: A review

Abstract: Emotional contagion, the emotional state‐matching of an individual with another, seems to be crucial for many social species. In recent years evidence on emotional contagion in different animal species has accumulated. However, despite its adaptative advantages and its presumed simplicity, the study and direct demonstration of this phenomenon present more complexities than previously thought. For these reasons, a review of the literature on emotional contagion in nonhuman species is timely to integrate current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 168 publications
(299 reference statements)
2
29
0
Order By: Relevance
“…Although emotional contagion was initially believed to be a prerogative of mammals and birds, recent empirical evidence demonstrates that simpler animals (Rose, 2002;Rose et al, 2014), are able to share emotions as well (Oliveira et al, 2017;Silva et al, 2019;Pérez-Manrique and Gomila, 2021). Our study complements these efforts and provides evidence of emotional contagion in the form of a reduction of anxiety-related behaviors propagating from a single, Citalopram-treated zebrafish to a group of untreated conspecifics.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Although emotional contagion was initially believed to be a prerogative of mammals and birds, recent empirical evidence demonstrates that simpler animals (Rose, 2002;Rose et al, 2014), are able to share emotions as well (Oliveira et al, 2017;Silva et al, 2019;Pérez-Manrique and Gomila, 2021). Our study complements these efforts and provides evidence of emotional contagion in the form of a reduction of anxiety-related behaviors propagating from a single, Citalopram-treated zebrafish to a group of untreated conspecifics.…”
Section: Discussionmentioning
confidence: 55%
“…Emotional contagion can influence social decision making and overall group performance through the spread of positive or negative emotions, which impact morale, motivation, and rapport. While this phenomenon has been widely documented across several taxa such as mammals (Langford et al, 2006;Zoratto et al, 2018) and birds (Adriaense et al, 2019), limited evidence of its occurrence has been reported in fish (Pérez-Manrique and Gomila, 2021). In an effort to contribute to a better understanding of emotional contagion, we studied how anxiety-related behavior can be propagated in groups of zebrafish by pharmacologically manipulating the behavior of a focal individual in the shoal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional contagion describes the tendency for emotional states to transmit from one individual to another leading to a convergence of emotional states (Decety & Ickes, 2011; Hatfield et al, 1993; Keysers et al, 2022). Emotional contagion has been documented to be widespread in the animal kingdom and is considered a pre-cursor to empathy (Pérez-Manrique & Gomila, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Emotional contagion has been documented to be widespread in the animal kingdom and is considered a pre-cursor to empathy (Pérez-Manrique & Gomila, 2022).…”
Section: Introductionmentioning
confidence: 99%